(untitled) (Publicaciones en Ciencias y Tecnología, 2019)
The technical efficiency for the cereal industry is conceived as an achievement when it is produced or obtained as much as possible from the available inputs. Efficiency analysis is presented through the application of Data Envelopment Analysis to eleven (11) markets of cereals in America for the corn, rice and wheat sectors in order to determine the technical efficiency in terms of projection or growth of each of them in the grain bag from cereal production, yield and exports. The indicators of the World Bank are used, where the agricultural factor of all the countries is related to global economic growth. It is obtained that the countries with high efficiency (100%) are Bolivia, Brazil, Costa Rica, and the Dominican Republic, being markets with production volumes less than 30MM. This analysis shows that the technical efficiency of the countries that are leaders in the grain market such as the US and Argentina are not technically efficient, presenting values of 86.8% and 39.3% respectively; and Chile with 4.2%. The most representative variables within technical efficiency are cereal production (64%) followed by exports (24%).